CIVIL AND FAMILY LAW: THE IMPACT OF CIVIL STATUS ON FAMILY RELATIONS IN UZBEKISTAN - Ellada Tengelbayevna, Sarsenbayeva (Antis Publisher, 2025)
Objective: This study examines the impact of civil status on family relations in Uzbekistan, focusing on the legal framework, historical evolution, and socio-legal implications. It explores how civil registration influences marital, parental, and inheritance rights within the broader context of civil and family law. Method: The research employs a qualitative approach, utilizing doctrinal legal analysis of legislative texts, judicial decisions, and academic literature. Comparative and historical methods are applied to assess the development and application of family law in Uzbekistan. Results: The findings reveal that civil status significantly affects family rights and obligations, with legal recognition playing a crucial role in defining marital legitimacy, parental authority, and inheritance distribution. Moreover, inconsistencies in registration procedures and legal interpretation create challenges for individuals navigating family law disputes. Novelty: This study contributes to the discourse on civil and family law in post-Soviet legal systems by highlighting the unique interplay between civil status and family relations in Uzbekistan. It offers insights into the legal complexities individuals face and suggests potential reforms to enhance legal clarity and protect family rights.